RESTRUCTURING OF THE MICRO-REGION GEOGRAPHIC PRESIDENTE PRUDENTE: STUDY AGROINDUSTRIAL MILK SECTOR IN THE CITY OF PRESIDENTE BERNARDES - SP - Francisco da Silva, Eliane Regina [UNESP]; Medeiros Hespanhol, Rosangela Aparecida de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2015)
The productive restructuring process implies the introduction of changes in management, production, organization and recruitment of the workforce in many different sectors of the economy and a global perspective. The goal of the research was to analyze the production and milk processing in the municipality of Presidente Bernardes, located in Geographic Micro Region of Presidente Prudente. The work was designed as a case study and the methodological procedures used were: literature and reading of selected material; collection and systematization of secondary data in the Agricultural Censuses of 1995/6 and 2006 Censuses IBGE 1991, 2000 and 2010 and the LUPA Project 1995/6 and 2007/8; development and application of a form to 56 dairy farmers (28 conventional and 28 settlers); interviews with representatives of dairy and local institutional agents. In this paper we present some of the results. In Geographical Microregion of Presidente Prudente, in particular, in the municipality of Presidente Bernardes, milk production is very important in generating income for small farmers. It was found that the best capitalized producers with greater information and that generally the higher input and specialized, tend to more easily withstand the impacts of the productive restructuring process.
Keywords: Productive restructuring; Rural areas; Milk production and processing; Technological changes; Presidente Bernardes